2020
DOI: 10.1097/sla.0000000000003299
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Aneurysm Repair With Inferior Mesenteric Artery Embolization for Preventing Type II Endoleak

Abstract: Objective: This study aimed to evaluate the effect of inferior mesenteric artery (IMA) embolization during endovascular aneurysm repair (EVAR) in patients at high risk of type II endoleak (T2EL) in randomized controlled trial (RCT). Summary Background Data: Several studies have demonstrated a reduction of T2EL by IMA embolization before EVAR. However, there have been no RCT confirming the efficacy of IMA embolization. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 30 publications
1
47
0
1
Order By: Relevance
“…Coil embolization of patent aortic side branches at time of EVAR to prevent T2ELs has also been described but has not yet become a mainstay prevention strategy. [10][11][12] Endovascular techniques have emerged as the preferred treatment modality for treatment of T2ELs, most often utilizing embolization via a trans-arterial or trans-lumbar approach. Regardless of the approach, endoleak treatment with coil embolization alone is associated with a high rate of reintervention and therefore, many investigators have refined their technique to incorporate ethylene vinyl alcohol copolymer or Onyx™ embolization.…”
Section: Introductionmentioning
confidence: 99%
“…Coil embolization of patent aortic side branches at time of EVAR to prevent T2ELs has also been described but has not yet become a mainstay prevention strategy. [10][11][12] Endovascular techniques have emerged as the preferred treatment modality for treatment of T2ELs, most often utilizing embolization via a trans-arterial or trans-lumbar approach. Regardless of the approach, endoleak treatment with coil embolization alone is associated with a high rate of reintervention and therefore, many investigators have refined their technique to incorporate ethylene vinyl alcohol copolymer or Onyx™ embolization.…”
Section: Introductionmentioning
confidence: 99%
“…We expected the IMAA to shrink secondarily with the decrease of the inner pressure of AAA by EVAR; and we could achieve a good result. When IMA is patent, the proximal site should be occluded, or the chimney technique 3) can prevent type II endoleak from IMA, 8) keeping the blood flow to the intestine. The aneurysm wall was enhanced in CT just before EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…19) Therefore, a patent IMA is thought to be an important cause of T2EL. Many studies 10,16,[20][21][22][23][24][25][26][27] have reported preoperative or intraoperative embolization attempts for the IMA and the success rate has been reported as ranged from 88.7%-100%. In these reports, embolization was attempted for 457 IMAs in total, with a remarkably high success rate of 95.8% has been reported.…”
Section: Discussionmentioning
confidence: 99%